Complete mitochondrial genomesequence of the hen harrier (Circus cyaneus). Issue 2 (3rd July 2018) - Gao, Xiaodong; Sun, Guolei; Xia, Tian; Zhao, Chao; Wei, Qinguo; Sha, Weilai; Zhang, Honghai
Abstract: In this study, the complete mitochondrial genome of the Hen Harrier ( Circus cyaneus ) was sequenced. The genome is found to be 18, 754 bp in length and has a base composition of A (31.7%), G (13.0%), C (31.2%), and T (24.1%). Similar to other Circus species, it contains a typically conserved structure including 13 protein-coding genes, 2 rRNA genes, 2 control region (D-loop), and 22 tRNA genes. A phylogenetic analysis between 17 species using 12 protein-coding genes proved that Accipiter gentilis is the most close to Circus cyaneus.